Krisis Lingkungan Dan Implikasinya Terhadap Keamanan Manusia: (Studi Kasus Pembuangan Limbah Nuklir Oleh Jepang) - Fariz Aditya; Raja Songkup Pratama; Florensia Silaban; Mantasia Hasibuan; Rahmi Siregar; Mario Fany Manurung (Student Research Journal, 2023)
The current environmental crisis has emerged as one of the most significant global issues, with the disposal of nuclear waste into the oceans garnering international attention. With the increasing production of nuclear waste from nuclear activities, such as nuclear power generation and nuclear use in industries, there arises a need to understand the environmental impact and threats to human safety associated with these actions. The disposal of nuclear waste can jeopardize marine ecosystems and biodiversity, creating contamination in seawater and marine organisms that can persist for decades to centuries. The risk of radiation exposure to humans through the consumption of contaminated seafood escalates, leading to potential serious health issues, including the risk of cancer. In this context, stringent policies and regulations in the management of nuclear waste and international cooperation are imperative. This research underscores the importance of identifying hazards arising from the disposal of nuclear waste into the open sea. Efforts to reduce and manage nuclear waste must be intensified through strict supervision by nuclear and environmental regulatory bodies. The disposal of nuclear waste can have serious impacts on the environment and human health by polluting seawater and marine organisms. Therefore, urgent actions are required to protect marine ecosystems, maintain ecological balance, and safeguard fisheries resources and biodiversity.